Access to Indole‐Fused Benzannulated Medium‐Sized Rings through a Gold(I)‐Catalyzed Cascade Cyclization of Azido‐Alkynes. Issue 51 (9th July 2021) - Greiner, Luca C.; Inuki, Shinsuke; Arichi, Norihito; Oishi, Shinya; Suzuki, Rikito; Iwai, Tomohiro; Sawamura, Masaya; Hashmi, A. Stephen K.; Ohno, Hiroaki
Abstract: Because benzannulated and indole‐fused medium‐sized rings are found in many bioactive compounds, combining these fragments might lead to unexplored areas of biologically relevant and uncovered chemical space. Herein is shown that α‐imino gold carbene chemistry can play an important role in solving the difficulty in the formation of medium‐sized rings. Namely, phenylene‐tethered azido‐alkynes undergo arylative cyclization through the formation of a gold carbene intermediate to afford benzannulated indole‐fused medium‐sized tetracycles. The reactions allow a range of different aryl substitution patterns and efficient access to these otherwise difficult‐to‐obtain medium‐sized rings. This study also demonstrates the feasibility of the semihollow‐shaped C‐dtbm ligand for the construction of a nine‐membered ring. Abstract : Golden keys close the loop : Starting from phenylene‐tethered azido‐alkynes, pharmaceutically relevant indole‐fused benzannulated eight‐membered rings were constructed by exploiting α‐imino gold(I) carbenes as key intermediates for the gold(I)‐catalyzed cascade reaction. The necessity of the C‐dtbm ligand for the cyclization to a more challenging nine‐membered ring is also demonstrated.